2017
DOI: 10.1039/c7cc04182a
|View full text |Cite
|
Sign up to set email alerts
|

“Inverted” porphyrins: a distorted adsorption geometry of free-base porphyrins on Cu(111)

Abstract: Based on density functional theory calculations combined with experimental results, we report and discuss an extremely distorted, "inverted" adsorption geometry of free-base tetraphenylporphyrin on Cu(111). The current findings yield new insights into a well-studied system, shedding light on the peculiar molecule-substrate interaction and the resulting intramolecular conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 31 publications
19
55
0
2
Order By: Relevance
“…In contrast 2H-TPP/Cu(111) has significant charge transfer, resulting in repulsive forces between the molecules that prevent molecular adlayer network formation. A similar result was observed by Lepper et al [78] who reported an inverted TPP on Cu(111) surface due to coordination of the two iminic nitrogen atoms to the Cu(111) surface via their lone pairs and thus significant charge transfer.…”
Section: Conformational Studies Of Meso-substituted Porphyrins On Subsupporting
confidence: 86%
“…In contrast 2H-TPP/Cu(111) has significant charge transfer, resulting in repulsive forces between the molecules that prevent molecular adlayer network formation. A similar result was observed by Lepper et al [78] who reported an inverted TPP on Cu(111) surface due to coordination of the two iminic nitrogen atoms to the Cu(111) surface via their lone pairs and thus significant charge transfer.…”
Section: Conformational Studies Of Meso-substituted Porphyrins On Subsupporting
confidence: 86%
“…Zweitens kann die intramolekulare Konformation aller hier untersuchten Freie‐Base‐Cyanporphyrine als “invertierte” Struktur identifiziert werden . Diese enthält zwei vertikal angeordnete Pyrrolringe und ist in Einklang mit der Beobachtung der hellen, zentralen Erhebungen in den submolekular aufgelösten Bildern in Abbildung b (vgl.…”
Section: Figureunclassified
“…] ist unabhängig von der Anzahl n der Cyangruppen (siehe SI, Tabelle S2). Dies ändert sich jedoch, wenn wir berücksichtigen, dass die Freie‐Base‐Porphyrine auf der Cu(111)‐Oberfläche nicht die Sattelkonformation der Gasphase, sondern die invertierte Struktur aufweisen . Die Cyangruppen reduzieren die Energie, die bei der Umwandlung der Sattelkonformation in die invertierte Geometrie aufgewendet werden muss (siehe SI, Tabelle S3).…”
Section: Figureunclassified
“…This structure is referred to as "inverted" and exhibits two protrusions, which are aligned along one of the three main crystallographic directions of Cu(111) (Figure 1c). [28] The strong similarity of the adsorption behavior and appearance of 2HTNP on Cu(111) to that of 2HTPP gives sufficient evidence to safely conclude that 2HTNP also adsorbs in the "inverted" structure. The four dimmer protrusions per molecule in Figure 1a resemble the flat lying naphthyl groups.…”
Section: Resultsmentioning
confidence: 92%
“…[23][24][25][26][27] On Cu(111), the strong chemical interaction between the iminic nitrogen atoms and the Cu substrate atoms leads to a peculiar intramolecular conformation, the so called "inverted" structure. [28,29] Based on the detailed knowledge of this structure, we herein now tackle the changes that occur when replacing the phenyl group by a naphthyl group to introduce a rotation axis in the molecular plane. For 2HTNP on Cu(111), assuming flat adsorption of the naphthyl groups, 16 different surface conformations are expected, including chiral and non-chiral species.…”
Section: Introductionmentioning
confidence: 99%